The Potential of Cellulose from the Sugar Palm (Arenga Pinnata) Seed Shell for Removal of Cr(Vi) Ions - Intan Lestari; Rahma Aini Sapitri; Diah Riski Gusti; Mounir El Achaby (Green Engineering Society, 2022)
Cr (VI) is persistent, bio-accumulative, toxic metal, unable to decompose in the environment, and accumulates in the human body through the food chain. The Cr(VI) ions can remove in aqueous solution by adsorption technique with cellulose extracted. Extract of cellulose were prepare from palm (Arenga pinnata) seed shell using acidified H2SO4 and bleaching methods. The cellulose have contained the hydroxyl (–OH) functional groups in structure, it can be an adsorbent for heavy metal ions. Cellulose was obtained with delignification and bleaching methods to break the bond between lignin and cellulose. The cellulose extracted were characterized by Fourier Transformation Infra-Red (FT-IR) and Scanning Electron Microscopy - Energy Dispersive X-Ray (SEM)-EDX. The adsorption process was conducted using pH, contact time, and concentration of Cr(VI) ions. The results showed that the optimum pH was obtained at pH 3 with an adsorption capacity is 0.88 mg/g. The optimum contact time was obtained at 120 minutes with an adsorption capacity is 0.89 mg/g. The optimum concentration was obtained at a concentration of 200 ppm with an adsorption capacity is 20.34 mg/g